LINC00857 Interacting with YBX1 to Regulate Apoptosis and Autophagy via MET and Phosphor-AMPKa Signaling - Wenmei Su; Lihui Wang; Huijie Zhao; Shengmin Hu; Yi Zhou; Chunfang Guo; Bin Wu; Lixia Li; Zhixiong Yang; David G. Beer; Guoan Chen (Elsevier, 2020)
Long noncoding RNA (lncRNA) LINC00857 has been reported to be upregulated in lung cancer and related to poor patient survival. It can regulate cell proliferation and tumor growth in lung cancer as well as several other cancers. However, the underlying molecular mechanisms that are regulated by LINC00857 are unclear. In this study, we found that LINC00857 silencing can impair cell proliferation in 14 different genomic alterations of lung cancer cell lines. These alterations are EGFR, KRAS, TP53, MET, and LKB1 mutations. The cell apoptosis and autophagy were induced upon LINC00857 silencing in lung cancer cells. Mechanistically, LINC00857 can bind to the Y-box binding protein 1 (YBX1) protein, prevent it from proteasomal degradation, and increase its nuclear translocation. LINC00857 regulated MET expression via YBX1 at a transcriptional level. Induced cell autophagy by LINC00857 knockdown was mainly through increased phosphor-AMP-activated protein kinase (p-AMPK)a. Collectively, LINC00857-YBX1-MET/p-AMPKa signaling is critical to regulate cell proliferation, apoptosis, and autophagy, which may provide a potential clinically therapeutic target in lung cancer.